Comparison of the Effects of Copper T and Levonorgestrel IUD on Proteoglycan Composition of Cervical Mucus - Yeşim Bayoğlu Tekin; Emine Seda Güvendağ Güven; Zihni Açar Yazıcı; Aynur Kırbaş; Figen Kır Şahin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of this study was to determine the effects of Copper T and Levonorgestrel IUD (LNG-IUD) on the proteoglycan composition of cervical mucus. STUDY DESIGN: This was a cross-sectional study that was conducted at a gynecology outpatient clinic of a University hospital for a six month period. The study participants were between 18-50 years old, using either Copper T or LNG-IUD for contraception. Cervical mucus samples were collected 7 days after the menstrual bleeding and the levels of hyaluronan (HA), heparin sulfate (HS) and sulfated-glycosaminoglycans (s-GAG) were evaluated. RESULTS: The levels of HA, HS and s-GAG in the Copper-T and LNG-IUD groups were higher than those of the controls. However, the difference was statistically significant only for s-GAG (p<0.001). CONCLUSION: Copper T and Levonorgestrel intrauterine contraceptive devices have significant effects on proteoglycan component of cervical mucus.